IMPLEMENTASI KITAB AN-NASHOR DALAM PEMBELAJARAN NAHWU DAN SHOROF (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
This qualitative library research aims to analyze the pedagogical structure of the adapted "An-Nashor" textbook, focusing on the gradation, selection, presentation, and repetition of its Nahwu and Shorof (Arabic grammar and morphology) materials. The study was motivated by a identified research gap: despite its widespread use, there has been a lack of in-depth analysis of the textbook's pedagogical claims, particularly its systematic organization of complex grammatical concepts. Using content analysis, with the digital and print versions of the "An-Nashor" textbook as the primary data source and 15 supporting journal articles and academic publications as secondary data, this research evaluates the material against principles of learning evaluation and Arabic language material development. The findings confirm that the textbook's content is organized in a systematic and gradual sequence, progressing from fundamental rules (qawa'id) to advanced discussions across nine thematic conversation groups. The study's novelty lies in its comprehensive examination of material gradation in an adaptive Arabic textbook, contributing to the theory of Arabic learning media development by demonstrating the effective implementation of pedagogical principles in a digital format. These results provide a crucial foundation for creating more structured and effective Arabic teaching materials.